2016
DOI: 10.1016/j.hrthm.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Associations between scar characteristics by cardiac magnetic resonance and changes in left ventricular ejection fraction in primary prevention defibrillator recipients

Abstract: BACKGROUND Left ventricular ejection fraction (LVEF) improves over time in 25%–40% of cardiomyopathy patients with primary prevention implantable cardioverter-defibrillators (ICD). The determinants of LVEF improvement, however, are not well characterized. OBJECTIVES We sought to examine the associations of clinical risk factors and cardiac imaging markers with changes in LVEF following ICD implantation. METHODS We conducted a retrospective analysis of cardiac magnetic resonance (CMR) images in 202 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Previous studies show that intermediate-signal-intensity LGE (i.e., gray zone) or inhomogeneous LGE, probably reflecting the mixture of fibrosis and normal myocardium, is significantly related to serious ventricular arrhythmia associated with ischemic cardiomyopathy and HCM [ 9 , 22 ]. By contrast, Zhang et al [ 23 ] have indicated that the clinical significance of gray zone and LGE burden may differ between ischemic and nonischemic cardiomyopathies. Fukushima et al [ 24 ] have shown that scarred apical aneurysm can induce ventricular tachyarrhythmias in patients with HCM.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies show that intermediate-signal-intensity LGE (i.e., gray zone) or inhomogeneous LGE, probably reflecting the mixture of fibrosis and normal myocardium, is significantly related to serious ventricular arrhythmia associated with ischemic cardiomyopathy and HCM [ 9 , 22 ]. By contrast, Zhang et al [ 23 ] have indicated that the clinical significance of gray zone and LGE burden may differ between ischemic and nonischemic cardiomyopathies. Fukushima et al [ 24 ] have shown that scarred apical aneurysm can induce ventricular tachyarrhythmias in patients with HCM.…”
Section: Discussionmentioning
confidence: 98%
“…Focal myocardial fibrosis detected by LGE imaging substantially increases the risk for life threatening arrhythmias in ICM [32][33][34]72]. Histologically, a myocardial scar is not always a uniform lesion.…”
Section: Ischemic Cardiomyopathymentioning
confidence: 99%
“…Cardiac magnetic resonance (CMR) is a highly effective imaging modality for the characterization of myocardial tissue as well as for the anatomical and the functional evaluation of the heart [23]. Several CMR findings are associated with arrhythmogenic substrates in CMs, with the late gadolinium enhancement (LGE) quantification and distribution pattern being the most well established [24][25][26][27][28][29][30][31][32][33][34]. The addition of CMR in the field of risk stratification for SCD of the CM patients is promising.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced predictive modelling would show the expected outcome not only with CRT therapies active but also with other device parameters. Ideal device settings could be generated which may evolve with the pa I to accurately predict degradation in ventricular function and hospitalisation as evidenced in patients with ICDs [32].…”
Section: Expert Commentarymentioning
confidence: 99%